2000
DOI: 10.1007/s004030000188
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of insulin-like growth factor-I in psoriasis as a paracrine growth factor: dermal fibroblasts play a regulatory role in developing psoriatic lesions

Abstract: To investigate the contribution of dermal fibroblasts to the development of psoriasis, we examined the expression of mRNA for insulin-like growth factor-I (IGF-I) and its regulator IGF-I binding proteins (IGFBPs) in psoriatic fibroblasts by RT-PCR. We also studied the effect of inflammatory cytokines including interferon gamma (IFN-gamma), tumor necrosis factor alfa (TNF-alpha), and IFN-alpha on the expression of IGF-I and IGFBPs in the fibroblasts. Semiquantitative analysis revealed that IGF-I mRNA expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
32
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(33 citation statements)
references
References 29 publications
1
32
0
Order By: Relevance
“…In addition to inflammatory cells, fibroblasts in transgenic skin may greatly contribute to epidermal hyperproliferation. It has been shown that psoriatic fibroblasts induce hyperproliferation of normal keratinocytes (Miura et al , 2000). Among fibroblast‐produced growth factors, KGF and IGF‐1 directly stimulate keratinocyte hyperproliferation (Miura et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to inflammatory cells, fibroblasts in transgenic skin may greatly contribute to epidermal hyperproliferation. It has been shown that psoriatic fibroblasts induce hyperproliferation of normal keratinocytes (Miura et al , 2000). Among fibroblast‐produced growth factors, KGF and IGF‐1 directly stimulate keratinocyte hyperproliferation (Miura et al , 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the number of cell nuclei positively stained for the Ki‐67 marker appears to correlate with the growth factor expression, which testifies a causative relationship between growth factor secretion in the dermis and proliferation of the epidermis. Similarly, psoriatic fibroblasts induce hyperproliferation of normal keratinocytes in skin equivalent model and express significantly higher insulin‐like growth factor 1 mRNA than control cells (3) .…”
Section: Discussionmentioning
confidence: 99%
“…In human umbilical vein endothelial cells, interleukin-1 (IL-1) was shown to induce a transient transcriptional 4.5-fold up-regulation of IGF-I (18), but the mechanism(s) was not demonstrated. In another study, primary dermal fibroblasts were used to investigate the effects of IFN-␥ on IGF-I mRNA expression (19). No regulation was detected, but the study was complicated by the presence of excess fetal bovine serum (10%) in the experimental conditions.…”
Section: Discussionmentioning
confidence: 99%